Dismantling the welfare state? Reagan, Thatcher, and the politics of retrenchment - Pierson, Paul 1959- (Cambridge Univ. Press, 1994)
This book offers a careful analysis of the politics of social policy in an era of austerity and conservative governance. Focusing on the administrations of Ronald Reagan and Margaret Thatcher, Pierson provides a compelling explanation for the welfare state's durability and for the few occasions in which each government was able to achieve significant cutbacks. Pierson's account draws on recent work in "historical institutionalism" and rational-choice theory to fashion an important argument about contemporary policy-making. The politics of retrenchment, he argues, is fundamentally different from that of welfare state expansion. The programs of the modern welfare state - the "policy legacies" of previous governments - generally proved resistant to reform. Hemmed in by the political supports that have developed around mature social programs, conservative opponents of the welfare state were successful only when they were able to divide the supporters of social programs, compensate those negatively affected, or hide what they were doing from potential critics. This book will be of interest to those in the fields of comparative public policy and political economy as well as to those concerned with the development of the modern welfare state.
Keywords: Geschichte 1979-1993; Politica social; Sociale politiek; Verzorgingsstaat; État providence; Welfare state; Wohlfahrtsstaat; Sozialpolitik; Grande-Bretagne - Politique sociale - 1979-; États-Unis - Politique sociale - 1981-1993; Großbritannien; USA; Great Britain -- Social policy -- 1979-; United States -- Social policy -- 1980-1993